The analysis of sleep quality of social studies vocational associate degree students and the factors that affect sleep quality - Kurt, Osman; Durna, Refika; Yılmaz, Alı Sırrı (My University, 2021)
Aim: This study aimed to analyze sleep quality of Social Sciences Vocational School students and the factors that affect sleep quality.Materials and Methods: This is a cross-sectional study. The first section included questions on sociodemographic attributes and sleep quality. In the second section, \"Pittsburgh sleep quality index\" was applied.Results: 44.3% of the students had good sleep quality. Poor sleep quality was 1.5 times higher among formal education students when compared to non-formal education students, 3.4 times higher among those without a regular diet when compared to those who did have, and 1.4 times higher among those who did not regularly exercise when compared to those who did.Conclusion: It was determined that non-formal education, irregular diet, and non-regular exercise were risk factors for poor sleep quality.
Keywords: Exercise; Sleep Quality; Vocational Higher Education School; Pittsburgh Sleep Quality Index